Bioethical aspects of human in vitro fertilisation - Di Giovanni, Alberto (Medicina e Morale, 1986)
My subject is human fertilisation 'in vitro' (acronym: IVF), extracorporeal therefore, not the artificial insemination of the husband's semen, carried out in the woman's womb (to complete the conjugal act: artificial insemination in the improper sense; while that outside the conjugal act is called artificial insemination in the proper sense, homologous; heterologous insemination, if with semen from a 'donor' outside the couple).